Morphological and molecular characterization of the toxic dinoflagellate Ostreopsis cf. ovata (Dinophyta) from Brazil (South Atlantic Ocean) - Gómez, Fernando (2017)
Ostreopsis cf. ovata is a toxic epiphytic dinoflagellate widely distributed in warm waters that often co-occur with species of the genera Coolia, Fukuyoa, Gambierdiscus and Prorocentrum. We investigated a strain isolated from the coast of Ubatuba, Brazil (South-West Atlantic Ocean) by light and epifluorescence microscopies; we also report molecular data based on the LSU rDNA and ITS markers. Cells were 35-65 µm in the dorso-ventral diameter and 20-40 µm wide. We obtained the sequence of a ~1900 base pair region of the rRNA gene cistron. In the LSU rDNA phylogeny, the sequences under the names O. ovata and O. cf. ovata branched into three clades. The ITS marker showed greater resolving power and the sequences of O. ovata/O. cf. ovata split into five clades. Our ITS sequence branched in a clade with sequences of strains from the Mediterranean Sea, European Atlantic coasts, subtropical NE Atlantic, other sequences from Brazil at Rio de Janeiro, and a few sequences from Japan. The cell dimensions and thecal plate arrangement were under the variability range reported in other ocean regions. Our observations confirm O. cf. ovata as the most commonly recorded species of Ostreopsis in the SW Atlantic Ocean. Ostreopsis cf. ovata co-occurred with Coolia malayensis in Brazil and Asia, but it has been commonly reported from the Mediterranean Sea, where C. malayensis has not yet been recorded; while Coolia malayensis has been reported from the Caribbean Sea, but not O. ovata. With the current knowledge, it is difficult to understand the factors that determine the biogeography of the tropical epiphytic dinoflagellates.